Development of the popular scientific book of Nepenthes diversity in Tanta District forest areas, Tabalong Regency: Validity and Practicality - Riya Irianti; Mahrudin Mahrudin (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2024)
Developing teaching materials based on local potential is necessary for introducing objects in the surrounding environment to support student learning. This is expected to broaden the insights and knowledge of students so that they become more familiar with and know the object of the material being taught. Wetlands are the dominant area in the South Kalimantan region and can be one of the learning resources in producing a product that can support learning at all levels of education; this can be in the form of local potential-based teaching materials, one of which is a popular scientific book. This study aims to describe the validity and practicality of popular scientific books based on the results of research on the Diversity of Semar Pockets (Nepenthes) Forest Areas in Tanta District, Tabalong Regency